Annotated Code of the State of Iowa Containing All the Laws of a General Nature Enacted by The Twenty-Sixth General Assembly at the Extra Session, Which Adjourned July 2, 1897 Page 1898 (Vol. 1, 1897) § 4775 - (:unkn) unknown (General Publisher, 1897)
Prohibited concealed carry and brandishing of pistols, revolvers, guns at another. Violators guilty of a misdemeanor and fined not more than one hundred dollars, or imrpsioned in the county jail not more than thirty days.
--
Keywords: CARRY - CONCEALED